N-terminal syndecan-2 domain selectively enhances 6-O heparan sulfate chains sulfation and promotes VEGFA165-dependent neovascularization - Corti, Federico; Wang, Yingdi; Rhodes, John M.; Atri, Deepak; Archer-Hartmann, Stephanie; Zhang, Jiasheng; Zhuang, Zhen W.; Chen, Dongying; Wang, Tianyun; Wang, Zhirui; Azadi, Parastoo; Simons, Michael (Nature communications, 2019)
The proteoglycan Syndecan-2 (Sdc2) has been implicated in regulation of cytoskeleton organization, integrin signaling and developmental angiogenesis in zebrafish. Here we report that mice with global and inducible endothelial-specific deletion of Sdc2 display marked angiogenic and arteriogenic defects and impaired VEGFA 165 signaling. No such abnormalities are observed in mice with deletion of the closely related Syndecan-4 (Sdc4) gene. These differences are due to a significantly higher 6-O sulfation level in Sdc2 versus Sdc4 heparan sulfate (HS) chains, leading to an increase in VEGFA 165 binding sites and formation of a ternary Sdc2-VEGFA 165 -VEGFR2 complex which enhances VEGFR2 activation. The increased Sdc2 HS chains 6-O sulfation is driven by a specific N-terminal domain sequence; the insertion of this sequence in Sdc4 N-terminal domain increases 6-O sulfation of its HS chains and promotes Sdc2-VEGFA 165 -VEGFR2 complex formation. This demonstrates the existence of core protein-determined HS sulfation patterns that regulate specific biological activities. Proteoglycans are glycosylated proteins that play a number of structural and signalling functions. Here, Corti, Wang et al. show that the N-terminal sequence of proteoglycan Syndecan-2 selectively increases 6-O sulfation of its heparan sulfate chains, and that this promotes formation of a ternary Sdc2/VEGFA/VEGFR2 complex leading to increased angiogenesis.